Implementasi Technological Pedagogical And Content Knowledge (TPACK) Pada Calon Guru Ekonomi Mahasiswa Angkatan 2021 Pendidikan Ekonomi di Universitas Siliwangi: The Implementation of Technological Pedagogical and Content Knowledge (TPACK) in Economics Teacher Candidates of the 2021 Cohort of Economics Education Students at Siliwangi University - Hafiani, Debi Rahma; Srigustini, Astri; Aisyah, Iis (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2025)
This study aims to describe the implementation of Technological Pedagogical and Content Knowledge (TPACK) among prospective economics teachers from the 2021 cohort of the Economics Education program at Siliwangi University. This research employed a qualitative approach with a descriptive method. Data was collected through interviews, observations, and documentation, which were then analyzed using the interactive model of Miles, Huberman, and Saldana. The findings indicate that the prospective economics teachers have implemented TPACK in their teaching practices, particularly in the aspects of Technological Knowledge (TK), Pedagogical Knowledge (PK), and Content Knowledge (CK). However, several challenges were identified in integrating technology, such as limited facilities and software proficiency. Despite these challenges, the students demonstrated creative and innovative teaching strategies in line with the demands of the 21st century. The study concludes that the students' TPACK abilities are quite good, yet require strengthening in the technical aspects of technology use for more optimal performance.